2018
DOI: 10.1029/2018gc007623
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater Seepage Into Sediments of the Shelf, Shelf Edge, and Continental Slope of the Canadian Beaufort Sea

Abstract: Long‐term warming of the continental shelf of the Canadian Beaufort Sea caused by the transgression associated with the last deglaciation may be causing decomposition of relict offshore subsea permafrost and gas hydrates. To evaluate this possibility, pore waters from 118 sediment cores up to 7.3‐m long were taken on the shelf and slope and analyzed for chloride concentrations and δ180 and δD composition. We observed downcore decreases in pore waters Cl− concentration in sediments from all sites from the inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 93 publications
0
28
0
Order By: Relevance
“…As a result, continuing warming causes not only advanced deepening of the IBPT but also thaw-through disintegration of the permafrost body at places such as fault zones, paleo-rivers, areas affected by thaw lakes, freshwater seepages into shelf sediments, and so-called pingo-like features, which provide subsea permafrost with heat and create migration pathways for CH 4 that is released from destabilizing hydrates [72][73][74]. A pingo is a mound of sediment-covered ice.…”
Section: Principal Scheme Of the Permafrost-hydrates Systemmentioning
confidence: 99%
“…As a result, continuing warming causes not only advanced deepening of the IBPT but also thaw-through disintegration of the permafrost body at places such as fault zones, paleo-rivers, areas affected by thaw lakes, freshwater seepages into shelf sediments, and so-called pingo-like features, which provide subsea permafrost with heat and create migration pathways for CH 4 that is released from destabilizing hydrates [72][73][74]. A pingo is a mound of sediment-covered ice.…”
Section: Principal Scheme Of the Permafrost-hydrates Systemmentioning
confidence: 99%
“…More recently, Gwiazda et al. (2018) showed that the freshening in pore water from the Beaufort Slope sediments is caused by regional groundwater flow and submarine groundwater that discharges as far as 150 km from the shore. Whether a similar set of mechanisms can explain the anomalous data observed at Site ARA06C‐JPC01 is a matter of interest.…”
Section: Resultsmentioning
confidence: 99%
“…The Chukchi Borderland is an adjacent fragment of continental crust extending north into the Canada Basin of the Arctic Ocean (Dove et al., 2014). The Beaufort Shelf, located in the eastern part of the Chukchi Sea, is up to ∼150 km wide with an average bathymetric gradient of 1 m/km (Gwiazda et al., 2018) (Figure 1).…”
Section: Regional Settingmentioning
confidence: 99%
“…Sediment cores showing sorting and layering adjacent to pockmarks reveal information about lacustrine sedimentary processes 96 and pockmark evolution 42 . Sediment coring campaigns with a percussion corer on August26–27, 2018 and March26–28, 2019 yielded six cores of 85 cm length or less from locations near W1 and W2 (Figure 3a).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms of pockmark formation involve upward fluid flows 20,30,40,42 including hydrodynamic blowouts, 27 submarine hydrate dissolution, 35,43 catastrophic dissolution of subterranean hydrates, 39 and explosive cryovulcanism events from compressed gas systems 44,45 . These mechanisms occur on a range of timescales spanning rapid, catastrophic explosions to gradual displacement over an undetermined length of time 27 .…”
Section: Introductionmentioning
confidence: 99%